Who goes back to school after birth? Factors associated with postpartum school return among adolescent mothers in the Eastern Cape, South Africa - Janina Jochim; Franziska Meinck; Elona Toska; Kathryn Roberts; Camille Wittesaele; Nontokozo Langwenya; Lucie Cluver (Taylor & Francis Group, 2023)
Early motherhood can negatively impact health, educational, and socio-economic outcomes for adolescent mothers and their children. Supporting adolescent mothers' educational attainment, and timely return to school, may be key to interrupting intergenerational cycles of adversity. Yet, there remains a paucity of evidence on the factors that are associated with mothers' postpartum return to school and the mediators of this process, particularly across sub-Saharan Africa where adolescent pregnancy rates remain high . This paper is based on interviews with 1,046 adolescent mothers from South Africa. Mothers who had returned to school after birth showed lower poverty, fewer repeated grades preceding the pregnancy, continued schooling during pregnancy, higher daycare/crèche use, more family childcare support, and lower engagement in exclusive breastfeeding within six months postpartum. Mediation analyses showed that lower poverty was directly associated with school return and via two indirect pathways: continued schooling during pregnancy and using daycare/crèche services. This study demonstrates that lacking childcare constitutes a major hurdle to mothers' school return which needs to be addressed in addition to socioeconomic and individual-level barriers. Policy makers and practitioners should consider supporting young mothers with combination interventions which include services supporting school retention during pregnancy and access to, and financial supplements for, daycare.